Polyphenol-Based Interventions in NAFLD: A Critical Analysis of TherapeuticEfficacy, Molecular Mechanisms, and Clinical Translation Barriers - A, Manikandan; J, Mukesh; M, Senthil (Eastern Journal of Medical Sciences, 2026)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is a chronic condition commonly associated with obesity and metabolic syndrome. Polyphenolic compounds, such as resveratrol and curcumin, have emerged as potential therapeutic agents due to their antioxidant and anti-inflammatory properties. Objective: This review aims to critically evaluate the therapeutic potential of resveratrol and curcumin in the management of NAFLD, focusing on their molecular mechanisms and clinical implications. Methods: The mechanisms through which resveratrol activates the AMPK and SIRT1 pathways to improve lipid metabolism and reduce oxidative stress are explored. Similarly, curcumin’s role in suppressing pro-inflammatory markers like TNF-α and IL-6 is examined. Results: Both resveratrol and curcumin demonstrate significant antioxidant and anti-inflammatory effects, contributing to improved liver function and lipid homeostasis. However, clinical translation of these compounds has been limited by challenges such as poor bioavailability, inconsistent dosing, and varying therapeutic outcomes. Conclusion: Despite these limitations, polyphenols show promise as adjunctive treatments for NAFLD. Advanced drug delivery systems and standardized therapeutic protocols are necessary to enhance their clinical efficacy. Further research is required to optimize the use of polyphenols in clinical practice.